Diets enriched in trans-11 vaccenic acid alleviate ectopic lipid accumulation in a rat model of NAFLD and metabolic syndrome - Jacome Sosa, M. Miriam (2014)
Trans11-18:1 (vaccenic acid, VA) is one of the most predominant naturally occurring trans fats in our food chain and has recently been shown to exert hypolipidemic effects in animal models. In this study, we reveal new mechanism(s) by which VA can alter body fat distribution, energy utilization and dysfunctional lipid metabolism in an animal model of obesity displaying features of the metabolic syndrome (MetS). Obese JCR:LA-cp rats were assigned to a control diet that included dairy-derived fat or the control diet supplemented with 1% VA. VA reduced total body fat (-6%), stimulated adipose tissue redistribution [reduced mesenteric fat (-17%) while increasing inguinal fat mass (29%)] and decreased adipocyte size (-44%) versus control rats. VA supplementation also increased metabolic rate (7%) concomitantly with an increased preference for whole-body glucose utilization for oxidation and increased insulin sensitivity [lower HOMA-IR (-59%)]. Further, VA decreased nonalcoholic fatty liver disease activity scores (-34%) and reduced hepatic (-27%) and intestinal (-39%) triglyceride secretion relative to control diet, while exerting differential transcriptional regulation of SREBP1 and FAS amongst other key genes in the liver and the intestine. Adding VA to dairy fat alleviates features of MetS potentially by remodeling adipose tissue and attenuating ectopic lipid accumulation in a rat model of obesity and MetS. Increasing VA content in the diet (naturally or by fortification) may be a useful approach to maximize the health value of dairy-derived fats.